2017
DOI: 10.1002/glia.23278
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal mouse cortical but not isogenic human astrocyte feeder layers enhance the functional maturation of induced pluripotent stem cell‐derived neurons in culture

Abstract: Human induced pluripotent stem (iPS) cell-derived neurons and astrocytes are attractive cellular tools for nervous system disease modeling and drug screening. Optimal utilization of these tools requires differentiation protocols that efficiently generate functional cell phenotypes in vitro. As nervous system function is dependent on networked neuronal activity involving both neuronal and astrocytic synaptic functions, we examined astrocyte effects on the functional maturation of neurons from human iPS cell-der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 67 publications
1
30
1
Order By: Relevance
“…This difference paralleled qPCR profiling showing that the maturation of hiPSC‐MN was less robust when mouse astrocytes were used and pharmacological testing showing only modest responses to drugs acting on neurotransmitter receptors in human/mouse cocultures This appears to be related to species differences rather than regional heterogeneity since rodent astrocytes were derived from the spinal cord. Our findings are in contrast to those of Lischka et al who found that neonatal mouse cortical but not isogenic human astrocyte feeder layers enhanced the maturation of iPSC‐N. It must be noted, however, that those investigators used a cortical patterning protocol to differentiate iPSC‐N, mouse forebrains to derive rodent astrocytes, and a patch‐clamp platform to record neuronal activity.…”
Section: Discussioncontrasting
confidence: 99%
“…This difference paralleled qPCR profiling showing that the maturation of hiPSC‐MN was less robust when mouse astrocytes were used and pharmacological testing showing only modest responses to drugs acting on neurotransmitter receptors in human/mouse cocultures This appears to be related to species differences rather than regional heterogeneity since rodent astrocytes were derived from the spinal cord. Our findings are in contrast to those of Lischka et al who found that neonatal mouse cortical but not isogenic human astrocyte feeder layers enhanced the maturation of iPSC‐N. It must be noted, however, that those investigators used a cortical patterning protocol to differentiate iPSC‐N, mouse forebrains to derive rodent astrocytes, and a patch‐clamp platform to record neuronal activity.…”
Section: Discussioncontrasting
confidence: 99%
“…Various studies have aimed to test neuron-astrocyte interactions using in vitro co-culture systems. These have included testing for interactions during development, such as the astrocytic effect on differentiation of precursor cells and stem cells (Johnson et al, 2007 ; Tang et al, 2013 ; Ehret et al, 2015 ; Lischka et al, 2017 ; Xie et al, 2017 ; Schutte et al, 2018 ), synchronization of neuronal network activity (Kuijlaars et al, 2016 ), and number of formed synapses (Pyka et al, 2011 ; Jones et al, 2012 ; Shi et al, 2013 ), and also the effect during disease states, such as in ALS (Kunze et al, 2013 ), thymine deficiency (Park et al, 2001 ), oxidative stress (Kidambi et al, 2008 ), and general neurotoxicity (Anderl et al, 2009 ). While the relevance of co-cultures of neurons and astrocytes has become more evident as more and more functions of astrocytes are discovered, their cumulative effect on the survival of low-density networks is seldom addressed and remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies using iPSC neurons and rodent astrocytes have highlighted the importance of including astrocytes in culture. Human-neuronal and rodent-astrocytic co-cultures demonstrate enhanced functional maturation, spiking activity, and maintenance of long-term electrical activity cf neurons alone ( Odawara et al, 2014 ; Lischka et al, 2018 ). It has recently been suggested that co-culture of human neurons with rodent astrocytes may generate matured spontaneous electrical activity to a greater extent than using human astrocytes ( Lischka et al, 2018 ).…”
Section: Ipscsmentioning
confidence: 99%